Pulsed and continuous wave doppler in heart lesions - HATLE, Liv (Archives of Acoustics, 1984)
Valvular obstructions and regurgitations can be diagnosed with either pulsed or CW Doppler. By recording the maximum velocities with CW Doppler the pressure drop across obstructions and across regurgitant valves can be obtained, permitting assessment of the severity of obstructions and providing information on the right heart pressures. Congenital lesions can be diagnosed, obstructions assessed and shunt size indicated.